Lymphatics and colorectal liver metastases: the case for sentinel node mapping. Issue 2 (19th July 2013) - Christophi, Christopher; Nguyen, Linh; Muralidharan, Vijayaragavan; Nikfarjam, Mehrdad; Banting, Jonathan
Abstract Background Hepatic resection remains the treatment of choice for patients with colorectal liver metastases (CLM). Indications for hepatic resection have been extended to include extrahepatic lymph node groups, resulting in increased survival benefits. The identification of specific lymph pathways and involved nodes is necessary to support the development of guidelines for a more focused approach to the management of this disease. The feasibility of sentinel node mapping should be investigated to define specific lymphatic groups involved in CLM. Methods Scientific papers published from 1950 to 2012 were sought and extracted from the MEDLINE, PubMed and University of Melbourne databases. Results Several studies have reported microscopic lymph node involvement in 10–15% of patients undergoing hepatic resection for CLM in which no macroscopic involvement was evident. In retrospect, over 80% of lymphadenectomies are proven unnecessary. Traditional imaging modalities have limited predictive value in detecting lymph node involvement. Sentinel node mapping has proved an extremely accurate tool in detecting lymph node involvement and can identify patients in whom lymphadenectomy may be beneficial. Conclusions Current imaging techniques are inadequate to detect microscopic lymph node involvement in patients with resectable CLM. The use of sentinel node mapping is proposed to identify nodal groups involved and provide management strategies.